1959
DOI: 10.1139/v59-232
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of the Heartwood Extractives of Tamarack (Larix Laricina (Du Roi) K. Koch)

Abstract: The acetone-soluble constituents of tlie heartwood of taniaracli have been investigated. The flavanonols taxifolin ancl aromadcndrin were isolated in 0.30 and 0.05% yield and a trace amount of quercetin was obtained. Tropolo~ies could not be detectecl, nor was there any evidence for resin acids. The major portion of the extract consisted of esters of ferulic, phthalic, andlong-chain fatty acids. Eicosanylfcrulatewasisolatedassucli, whereas the other constituents were iclentified after saponification. Gas liq~l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Nair and von Rudloff (1959Rudloff ( , 1960) studied and compared chemical composition of heartwood extractives of Tamarack (Larix laricina) and Alpine larch (Larix lyalii). Norin and coauthors (1965) determined the structures and confi gurations of the diterpenoids larixol, larixyl acetate and 13-epimanool, which were isolated from the oleoresin of European larch.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Nair and von Rudloff (1959Rudloff ( , 1960) studied and compared chemical composition of heartwood extractives of Tamarack (Larix laricina) and Alpine larch (Larix lyalii). Norin and coauthors (1965) determined the structures and confi gurations of the diterpenoids larixol, larixyl acetate and 13-epimanool, which were isolated from the oleoresin of European larch.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…1). I t .hydrolyzed with difficulty, causing considerable degradation of the ferulic acid moiety, and its infrared absorption spectrum was similar to that of the eicosculyl ferulate isolated from the heartwood of L. laricina (1). The 11011-saponifiable portion was co~nposed of a mixture of alcohols which failecl to crystallize and which could not be resolved by distillation.…”
Section: Cas\dian Jolrs-almentioning
confidence: 77%
“…One study identified anti-tumor active principles [labdanetype diterpenes (Pichette et al, 2006)], while others studied the effect of the environment on phytochemicals components of Larix larix [volatiles (Nair and Von Rudloff, 1959;Von Rudloff, 1987;Powell and Raffa, 1999), phenolics (Niemann, 1969;Niemann and Bekooy, 1971) and diterpenes (Mills, 1973)]. Hence, ours is the first study that focuses on the identification of the active principles responsible for the adipogenic effect as putative antidiabetic mechanism of Larix laricina, as used by traditional Healers in Canadian Aboriginal populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant amounts of rhaponticin (compound 9) were obtained from the fraction LLE-10. The known compounds 2-10 were identified by comparison of their spectroscopic data with those already reported in the literature (Nair and Von Rudloff, 1959;Caputo et al, 1973;Mills, 1973;Markham, 1976;Kashiwada et al, 1984;Rajasekhar and Subbaraju, 2000;Xie et al, 2003;Xue et al, 2004;Yang et al, 2005;Pichette et al, 2006;Chen et al, 2009;Pacheco et al, 2009). The identification of the new compound (compound 1) was conducted by 1D NMR ( 1 H, 13 C, DEPT) and 2D NMR (NOESY, COSY, HMQC and HMBC) analysis, as described further below.…”
Section: Adipogenic Activity Of Larix Laricina Fractions and Compoundsmentioning
confidence: 99%